2005
DOI: 10.1093/ps/84.6.894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-mannanase in corn-soy diets on commercial leghorns in second-cycle hens

Abstract: beta-Mannanase (Hemicell) is a unique enzyme-based feed ingredient that can hydrolyze beta-mannan, an antinutritional fiber in feed. Because soybean meal contains beta-mannan and its derivatives, addition of beta-mannanase may improve soybean-meal utilization. The purpose of this study was to evaluate the effect of beta-mannanase on performance of commercial Leghorns fed corn-soybean meal based diets. In this experiment, 3 diets were formulated. The metabolizable energy content for diet 1 (high-energy diet) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
67
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 12 publications
7
67
0
5
Order By: Relevance
“…Such improving feed conversion as result of enzyme supplementation in the diet was caused significant increase of egg production and at the same time the insignificant differences in feed consumption among treatments. These results are supported with the finding of Wu et al (2005), who supplemented diets with enzyme and reported that despite an increase in egg production, feed intake did not change (p !0.05). Mandal et al (2000) in their study with broilers showed that probiotics as alternating antibiotics in the diets of these birds resulted in improved feed conversion ratio (FCR) and body weight gain.…”
Section: Effect Of Enzyme and Probiotic On Feed Intake Feed Conversisupporting
confidence: 88%
“…Such improving feed conversion as result of enzyme supplementation in the diet was caused significant increase of egg production and at the same time the insignificant differences in feed consumption among treatments. These results are supported with the finding of Wu et al (2005), who supplemented diets with enzyme and reported that despite an increase in egg production, feed intake did not change (p !0.05). Mandal et al (2000) in their study with broilers showed that probiotics as alternating antibiotics in the diets of these birds resulted in improved feed conversion ratio (FCR) and body weight gain.…”
Section: Effect Of Enzyme and Probiotic On Feed Intake Feed Conversisupporting
confidence: 88%
“…The significant effect of Hemicell on immunity of broilers may be explained by the findings of Wu et al (2005) who reported that substrate of Hemicell entering the intestinal tract resulted in a reduction of the β-mannan content associated with a reduction of innate immune stimulation. An important mode of action is a reduction in innate immune stimulation associated with a reduction in the β-mannan content of substrate entering the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…But the PKM also contains 35 40% mannans, which is poorly digestible by poultry (Sundu et al, 2006). Therefore, supplementation of its respective enzyme, mannanase has been recommended (Wu et al, 2005;Sundu et al, 2006). In addition, several poultry studies (Sundu et al, 2006;Chong et al, 2008;Zanu et al, 2012) showed that the appropriate level of PKM inclusion had encouraged the feed intake in laying hens.…”
Section: Introductionmentioning
confidence: 99%